2018
DOI: 10.1007/s10067-018-4022-5
|View full text |Cite
|
Sign up to set email alerts
|

Reactive arthritis: update 2018

Abstract: At this time, reactive arthritis (ReA) is considered to be part of the spectrum of the spondyloarthritis, previously known as Reiter's syndrome, and refers to an infection induced systemic illness, characterized by a sterile synovitis occurring in a genetically predisposed individual, secondary to an infection localized in a distant organ/system, but also accompanied with multiple extra articular manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 38 publications
0
62
0
3
Order By: Relevance
“…But, Townes et al have stated that relative risk RR is higher for women (RR 1.5 vs. males) and adults (RR 2.5 vs. children) [9]. However, when it comes to genitourinary infections, the risk is higher for men than women with 9:1 ratio [1]. Another study has shown that females are more exposed than male [10].…”
Section: Is the Epidemiology Of Rea Changing?mentioning
confidence: 99%
See 1 more Smart Citation
“…But, Townes et al have stated that relative risk RR is higher for women (RR 1.5 vs. males) and adults (RR 2.5 vs. children) [9]. However, when it comes to genitourinary infections, the risk is higher for men than women with 9:1 ratio [1]. Another study has shown that females are more exposed than male [10].…”
Section: Is the Epidemiology Of Rea Changing?mentioning
confidence: 99%
“…In ReA genitourinary transmission, Chlamydia trachomatis (Ct) is the most common cause followed by Ureaplasma urealyticum and other less common germs [1].…”
Section: What Are the Pathophysiologic Model Advances?mentioning
confidence: 99%
“…30 These perturbations are highly dependent on host genetic background. 31 In humans, the most obvious examples of the gut-joint connection are reactive arthritis, described in 1916 by Noël Fiessinger and Emile Leroy, 32 which results after infection by enteropathogenic (and uropathogenic) bacteria, 33 and enteropathic arthritis, described in 1929 by J Arnold Bargen, 34 which is a sequala of inflammatory bowel disease (IBD) and can parallel colitis exacerbations (figure 1). 35 Another example is ankylosing spondylitis, where terminal ileal biopsies demonstrate distinct microbial signatures driven by several core families of bacteria.…”
Section: What Is Known About the Microbiome In Autoimmune Diseasesmentioning
confidence: 99%
“…Since IL-17 has been found to play an important role in the pathogenesis of spondyloarthropathy [53], it has been shown that IL-17a monoclonal antibody is effective in the treatment of ankylosing spondylitis, psoriatic arthritis and rheumatoid arthritis without serious adverse events [54][55][56]. At present, there are only three IL-17a monoclonal antibodies on the market: secukinumab, ixekizumab and brodalumab.…”
Section: Interleukin-17a Monoclonal Antibodymentioning
confidence: 99%